The landscape of disparities in obstetric neurocritical care and a path forward - Mittal, Shilipi; Alsbrook, Diana; Okwechime, Remi T.; Iqbal, Farhana; Nobleza, Christa O'Hana S. (Frontiers in Neurology, 2023)
Health disparities in the obstetric population affect maternal morbidity and mortality. In the past years, there has been no significant improvement in disparities in care in the obstetric population. Patients who are pregnant are known to have a higher risk of pregnancy-associated neurologic conditions such as stroke and intracerebral hemorrhage. They can also experience concomitant neurocritical care disease states such as status epilepticus and traumatic brain injury. Studies exploring the disparities of care among pregnant patients who are neurotically ill are lacking. We aim to provide the landscape of disparities of care among the obstetric neurocritically-ill population and provide potential actionable opportunities to address these disparities in care.